A myriad of roles of dendritic cells in atherosclerosis. (6th July 2021) - Zhao, Yanfang; Zhang, Jing; Zhang, Wenjie; Xu, Yuekang
Abstract: Atherosclerosis is an inflammatory disease with break‐down of homeostatic immune regulation of vascular tissues. As a critical initiator of host immunity, dendritic cells (DCs) have also been identified in the aorta of healthy individuals and atherosclerotic patients, whose roles in regulating arterial inflammation aroused great interest. Accumulating evidence has now pointed to the fundamental roles for DCs in every developmental stage of atherosclerosis due to their myriad of functions in immunity and tolerance induction, ranging from lipid uptake, efferocytosis and antigen presentation to pro‐ and anti‐inflammatory cytokine or chemokine secretion. In this study we provide a timely summary of the published works in this field, and comprehensively discuss both the direct and indirect roles of DCs in atherogenesis. Understanding the pathogenic roles of DCs during the development of atherosclerosis in vascular tissues would certainly help to open therapeutic avenue to the treatment of cardiovascular diseases. Abstract : DCs play important roles in the development of atherosclerosis via both direct and indirect approaches, which could be either pro‐atherogenic or atheroprotective.